2022
DOI: 10.1177/17455057221111326
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial issues and coping mechanisms of pregnant and postnatal women diagnosed with COVID-19: A qualitative study

Abstract: Objective There is a paucity of data on the psychosocial issues and coping mechanisms among pregnant and postnatal women with COVID-19 infection. We, therefore, aimed to explore the psychosocial issues and coping mechanisms of pregnant and postnatal women diagnosed with COVID-19 at tertiary-level hospitals. Methods This was a qualitative phenomenological study conducted in 2021 with a sample size of 16 women admitted at two referral hospitals serving as COVID-19 admission facilities for pregnant and postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The responses were transcribed verbatim and counter-checked to verify accuracy through an iterative process that was equally applied to the generation of themes hence adding to the credibility of the study. Whilst the results are not generalizable as is the case for qualitative studies, 40 there is immense value in the themes identified which the University could put into consideration and inform policy when online learning is engaged for medical students as their learning needs are unique.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…The responses were transcribed verbatim and counter-checked to verify accuracy through an iterative process that was equally applied to the generation of themes hence adding to the credibility of the study. Whilst the results are not generalizable as is the case for qualitative studies, 40 there is immense value in the themes identified which the University could put into consideration and inform policy when online learning is engaged for medical students as their learning needs are unique.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…Indeed, studies have demonstrated how the pandemic impacted the quality of maternal healthcare, including inpatient services [35,36]. Studies also document the type and amount of stigmatization experienced by pregnant persons who tested positive for COVID [37][38][39]. This is concerning, given the degree to which the behaviors and choices of pregnant persons have been scrutinized before the pandemic [40].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are worsened by anti-vaccine movements present among society, healthcare workers, and various media platforms misleading many citizens ( 57 ). Counter and positive context-specific messages are key in ensuring constant debunking of these myths and misconceptions such as the HPV vaccine does not cause ovarian insufficiency as early claims were based on case reports ( 58 ).…”
Section: Discussionmentioning
confidence: 99%